PERANAN MUSEUM SINGHASARI SEBAGAI SUMBER BELAJAR BAGI WISATAWAN PELAJAR - Farhan, Muhammad (Universitas Negeri Malang, 2024)
Abstract: This research was conducted with the aim of knowing the role of the Singhasari Museum as a learning resource for student tourists and describing the suitability of the Singhasari Museum as a learning resource. This research uses a qualitative approach with descriptive research type. The data obtained is described in detail and coherently about the role of the Singhasari Museum as a learning resource for student tourists. The techniques used to obtain data are observation, interviews and documentation. The collected information will be analyzed and presented in the form of descriptive descriptions that will answer existing research problems in the field. Based on the research results, two conclusions were obtained. First, the Singhasari Museum is worthy of being used as a learning resource for student tourists by meeting the criteria, namely the goals to be achieved, economical, practical and simple, easy to obtain, and flexible. Through collection objects, the Singhasari Museum provides information to visitors and cannot be separated from the historical values left behind by the discoveries of the Singhasari Kingdom. Having a tour guide also provides more knowledge to student tourists who visit the Singhasari Museum. The Singhasari Museum also provides complete facilities for student tourists. Second, the role of the Singhasari Museum as a learning resource for student tourists can be known through tourist visits made at the Singhasari Museum. There are several factors behind student tourists coming to the museum, namely push factors and pull factors. It is known that there are various activities of student tourists during their visit to the Singhasari Museum, namely gathering information, history learning activities, group discussions and study tours. The benefits that student tourists get after visiting the Singhasari Museum are growing a sense of concern for historical heritage, enriching information, providing new nuances of learning, developing curiosity and insight, and as a means of recreation in the midst of routine. Abstrak: Penelitian ini memiliki tujuan mengetahui peranan Museum Singhasari sebagai sumber belajar bagi wisatawan pelajar serta mendeskripsikan bagaimana kelayakan dari Museum Singhasari sebagai sumber belajar. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Data yang diperoleh dideskripsikan secara detail dan runtut tentang peranan Museum Singhasari sebagai sumber belajar bagi wisatawan pelajar. Teknik yang digunakan untuk memeroleh data yaitu observasi, wawancara, dan dokumentasi. Dari terkumpulnya informasi akan dianalisis dan dipaparkan dalam bentuk uraian deskriptif yang akan menjawab permasalahan penelitian yang ada di lapangan. Berdasarkan hasil penelitian diperoleh dua simpulan. Pertama, Museum Singhasari layak dijadikan sebagai sumber belajar bagi wisatawan pelajar dengan memenuhi kriteria yaitu tujuan yang ingin dicapai, ekonomis, praktis dan sederhana, gampang didapat, serta fleksibel. Melalui benda koleksi, Museum Singhasari memberikan informasi kepada pengunjung dan tak lepas dari nilai-nilai sejarah yang tertinggal dari penemuan Kerajaan Singhasari. Adanya pramuwisata juga memberikan pengetahuan lebih kepada wisatawan pelajar yang berkunjung ke Museum Singhasari. Museum Singhasari juga memberikan fasilitas lengkap bagi para wisatawan pelajar. Kedua, peran Museum Singhasari sebagai sumber belajar bagi wisatawan pelajar dapat diketahui melalui kunjungan wisata yang dilakukan di Museum Singhasari, terdapat beberapa faktor yang melatari wisatawan pelajar datang ke museum yakni faktor pendorong (push factor) dan faktor penarik (pull factor). Diketahui ragam kegiatan wisatawan pelajar selama berkunjung di Museum Singhasari yakni menggali informasi, kegiatan pembelajaran sejarah, diskusi kelompok, dan studi wisata. Manfaat yang diperoleh wisatawan pelajar setelah berkunjung ke Museum Singhasari yaitu menumbuhkan rasa kepedulian terhadap peninggalan Sejarah, memperkaya informasi, memberikan nuansa pembelajaran yang baru, mengembangkan rasa keingintahuan dan wawasan yang dimiliki, serta sebagai sarana rekreasi di tengah rutinitas.